PENGARUH EKUITAS MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC HONDA VARIO - Siti Muniah; Apriatni EP; Sendhang Nurseto (Universitas Diponegoro, 2016)
CV. Cendana Motor Sukorejo is one of the official Honda dealer in Sukorejo. Over the last 5 years of sales, HondaVario had fluctuating movement. In 2013, Honda Vario sales amounted to 133,36%. But in 2014, Honda Vario haddecreased to 39,23%. This research aims to determine the extent of the influence of brand equity (X1) andpromotion (X2) against the purchase decisions (Y) Honda Vario motorcycle in CV. Cendana Motor Sukorejo. Thistype of research is explanatory research, with a population that is all consumer who purchase and use of HondaVario motorcycles. The sample used in this research as many as 100 respondents with techniques of sampling useda purposive Sampling method. Data collection technique on this research using interview and questionnaire. Dataanalysis technique using validity test, reliability test, simple linear regression, multiple linear regression, t test andF test with the tools SPSS 16.0. The result of this research shows that brand equity variable has significant effect tothe purchase decisions of Honda Vario motorcycle 52,4%. The promotion variable has also significant to thepurchase decisions of Honda Vario motorcycle 34,9%. Brand equity an promotion variable have effect to thepurchase decisions 53,1%. According to the result of this research, inferential that the customer perception aboutbrand equity and promotion in the strong category and the purchase decisions has significant effect. So, thecompany suggested to strengthen brand equity and increasing marketing strategy especially sales promotion ofHonda Vario motorcycle.